A study on back irradiation flat panel detector with crystal silicon based x-ray CMOS image sensor. (February 2019) - Kim, Myung Soo; Kim, Yewon; Lim, Kyung Taek; Kang, Donguk; Cho, Gyuseong
Abstract: In order to find an image of small-sized defects in a subject that consists of a high Z-number material, the X-ray image sensor should have a high spatial and a high radiometric resolutions for the high energy X-ray imaging. Because the sensors based on thin film transistors cannot make small size pixels, the sensors based on CMOS technology have been considered. Moreover, in order to overcome the degradation of the spatial resolution with a thick scintillator, the back irradiation (BI) method was proposed. In this study, we verified the combination of the BI method and the sensor based on the CMOS technology. From the results of the light yield, which is related to the radiometric resolution, the thin wafer is one of the important factors for enhancing the collection efficiency of the BI method, especially in the collection of the soft X-ray. In addition, the high voltage on the tube helps improve the efficiency of the BI method. From the results of the modulation transfer function, which is related to the spatial resolution, the BI method has a better result compared with the conventional method, which is called front irradiation, no matter the thickness of the scintillators. Highlights: The back irradiation method with CMOS X-ray image sensor was designed and tested. The light yield might be increased when the thin silicon wafer is used. The MTF is increased 38% with thick scintillator.